Foresight vision in Adeeb Kamal al-Din`s poetry - Yasir Kaghim , Lect. Dr. Adil (Basra studies journal, 2026)
There is a visionary outlook in the poetry of Adib Kamal al-Din that represents the poet's voice regarding this poetic experience, on both the form and content levels. This vision, adopted by the poet himself, is part of his artistic forebodings and the questions swirling within him, questions that are interwoven with a constant sense of the universe and existence. Therefore, the poet attempts to evoke questions which he projects onto a number of his poetic images that represent his intellectual journey and creative experience. He transforms these images into a clear response to the issues of his time through a series of paradoxes presented through the voices of prophets, alluding to what the Quran states. He draws lessons and wisdom from their experiences, employing a literal approach that allows him to give voice to the letters